The Effect of Performance Assessment and Work Experience on Employee Career Development in PT. Cipta Niaga Semesta Lahat - Titi Hasanah; Melia Andayani; Hestin Hestin; Pahlan Pahlan (Green Publisher Indonesia, 2022)
This study aims to determine and analyze the effect of performance appraisal and work experience on employee career development and the effect of performance appraisal on career development and the effect of work experience on employee career development at Pt.Cipta Niaga Semesta Lahat. The sample in this study were 36 employees of PT Cipta Niaga Semesta Lahat. So the sampling method used in this study is a census sampling method, which collects data from the entire population. The analytical method in this study uses quantitative analysis with the help of the SPSS program. Based on the results of data processing using SPSS the regression equations obtained are: The equation can be concluded that if there is no performance appraisal variable (X1), work experience variable (X2), then the value of work experience is 8,216. If the performance appraisal variable (X1) is increased by one unit, it will temporarily increase the career development variable (Y) by 0.455. If the work experience variable (X2) is increased by one unit, it will increase the career development variable (Y) by 0.79. The value of the coefficient of determination () based on the SPPS data processing table is 0.610. This means that the influence of the variable career development of employees at Pt. Cipta Niaga Semesta Lahat can be explained by the variables of performance appraisal and work experience with a contribution of 61%, while the remaining 39% can be explained by other variables not included in this research model.